2019
DOI: 10.15666/aeer/1702_20332041
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Predatory Mite Phytoseiulus Persimilis (Acari: Phytoseiidae) in the Control of Twospotted Spider Mite (Tetranychus Urticae Koch, Acari: Tetranychidae) at Greenhouse Cucumber Production in Tokat Province, Turkey

Abstract: The effectiveness of the predatory mite, Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae), as a suppressive agent of the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), was evaluated on greenhouse cucumber at predator:prey release ratios of 1:5, 1:15, and 1:30. Releases at each predator:prey ratio were made at 30 T. urticae densities per leaf. Evaluation was initiated 4 days after the release. On the under side of the leaves which were selected randomly from the lower, mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…In addition, we report a positive correlation between the populations of P. persimilis and the two-spotted spider mites, suggesting the establishment of P. persimilis in the integrated pest management greenhouse with two-spotted spider mite serving as a food source. Our data are supported by several studies showing the predation efficiency and oviposition rate of P. persimilis when fed a diet consisting of two-spotted spider mites (Masoud 2007;Gillian 2008;Moghadasi et al 2016;Fathipour et al 2017;Yanar et al 2019;Ahmadi et al 2020). In the control greenhouses at sites A and B, seven and 10 insecticides and acaricides were sprayed, respectively, to control two-spotted spider mite populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, we report a positive correlation between the populations of P. persimilis and the two-spotted spider mites, suggesting the establishment of P. persimilis in the integrated pest management greenhouse with two-spotted spider mite serving as a food source. Our data are supported by several studies showing the predation efficiency and oviposition rate of P. persimilis when fed a diet consisting of two-spotted spider mites (Masoud 2007;Gillian 2008;Moghadasi et al 2016;Fathipour et al 2017;Yanar et al 2019;Ahmadi et al 2020). In the control greenhouses at sites A and B, seven and 10 insecticides and acaricides were sprayed, respectively, to control two-spotted spider mite populations.…”
Section: Discussionsupporting
confidence: 88%
“…However, in the site A control greenhouse, seven consecutive acaricide sprays failed to keep the two-spotted spider mite population below damaging levels, leading to the premature termination of production in the control greenhouse. Yanar et al (2019) reported similar results in a screenhouse trial in Tokat province, Turkey, which showed higher control of two-spotted spider mite populations on cucumber plants by P. persimilis mites compared to conventional acaricide applications.…”
Section: Discussionsupporting
confidence: 57%
“…Application of predatory mites for biological control is a well‐established method against spider mite pests around the world, with Phytoseiulus persimilis Athias‐Henriot (Acari: Phytoseiidae) being the most used predator for the control of the serious invasive pest, Tetranychus urticae Koch (Acari: Tetranychidae). 44 , 45 , 46 , 47 , 48 These reports mainly evaluated the effectiveness of biological control based on the relationship between the release of P. persimilis and population size changes of T. urticae , assuming that the spider mite population decline is caused by direct predation. However, nonconsumptive effects of predators on prey fitness and forage may also contribute to pest biological control but have been rarely evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…At site II, we observed P. persimilis in nearby open field beans about three months after the trial concluded. The predation activity of P. persimilis has been widely documented in both open fields and GH crops [ 28 , 32 , 37 ]. The efficacy of P. persimilis is correlated with the predator-prey release ratios and the timing of mite introduction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%